(untitled) (Acta Scientiarum. Technology, 2025)
Taiwan’s declining birth rate and the lack of personnel in the national army have worsened. In particular, the loss of human resources caused by the lack of career competitiveness among national army officers has been increasing daily. Effective career competitiveness not only aligns personal interests with job roles but also enhances self-confidence and increases workplace value. The professional competitiveness of military officers depends on the nurturing of the Military Academy Education System (MAES), which involves the comprehensive consideration and evaluation of individual performance such as university education (UE), sport and combat ability (SCA), and military skill (MS); it is a complex multiple attribute decision making (MADM) problem. However, the current method fails to effectively consider individual attributes, which may result in cadets being assigned to unsuitable units or positions, leading them to consider retirement and thereby weakening national defense capabilities. To solve this problem, this research integrated the technique for order preference by similarity to an ideal solution (TOPSIS) and three-dimensional importance-performance analysis method to propose a novel three-dimensional TOPSIS (3D-TOPSIS) model, aimed at improving the evaluation process of cadets’ career competitiveness. The results demonstrate that this model accurately assesses cadets’ attributes and distribution, providing valuable insights for personnel assignments and the allocation of educational resources.